Mini-Review on Targeted Treatment of Desmoplastic Small Round Cell Tumor - Bexelius, Tomas S.; Wasti, Ajla; Chisholm, Julia C. (Frontiers in Oncology, 2020)
Desmoplastic small round cell tumour (DSRCT) is a devastating disease which most commonly affects adolescents, with a male predominance. Despite the best multimodality treatment efforts, most patients will ultimately not survive more than 3-5 years after diagnosis. Some research trials in soft-tissue sarcoma and Ewing sarcoma include DSRCT patients but few studies have been tailored to the specific clinical needs and underlying cytogenetic abnormalities characterizing this disease such as the typical EWSR1-WT1 gene fusion. Downstream activation of EWSR1-WT1 gene fusion includes signaling pathways of platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), and insulin growth factor (IGF)-1. Other biological pathways that are activated and expressed in DSRCT cells include endothelial growth factor receptor (EGFR), androgen receptor pathway, c-KIT, MET, and transforming growth factor (TGF) beta. Investigation of somatic mutations, copy number alterations (CNA), and chromosomes in DSRCT samples suggests that deregulation of mesenchymal-epithelial reverse transition (MErT)/epithelial-mesenchymal transition (EMT) and DNA damage repair (DDR) may be important in DSRCT. This mini review looks at known druggable targets in DSRCT and existing clinical evidence for targeted treatments, particularly multityrosine kinase inhibitors such as pazopanib, imatinib and sorafenib alone or in combination with other agents such as mTOR (mammalian target of rapamycin) inhibitors. The aim is to increase shared knowledge about current available treatments and identify gaps in research to further efforts towards clinical development of targeted agents.